The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3390/w12010033
|View full text |Cite
|
Sign up to set email alerts
|

Pilot Studies and Cost Analysis of Hybrid Powdered Activated Carbon/Ceramic Microfiltration for Controlling Pharmaceutical Compounds and Organic Matter in Water Reclamation

Abstract: This paper addresses the enhanced removal of pharmaceutical compounds (PhCs), a family of contaminants of emerging concern, and effluent organic matter (EfOM) in water reclamation by powdered activated carbon/coagulation/ceramic microfiltration (PAC/cMF). Four chemically diverse PhCs are targeted: ibuprofen (IBP), carbamazepine (CBZ), sulfamethoxazole (SMX) and atenolol (ATN). Pilot assays (100 L/(m 2 h), 10 mg Fe/L) run with PhC-spiked sand-filtered secondary effluent and 15 mg/L PAC dosed in-line or to a 15-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 14 publications
(10 reference statements)
2
7
0
Order By: Relevance
“…Overall, and under the conditions tested, equivalent removals of pesticides and NOM were obtained with inline PAC dosing and to a contact tank in trial 1 using the same PAC dose, while in trial 2 a higher inline PAC dose was apparently required (50% higher in the conditions tested, though further testing with other PAC doses would be necessary to confirm it). Results from trial 1 are in agreement with those observed by Ivancev-Tumbas et al [25] for p-nitrophenol removal from tap water, whereas results from trial 2 are more in agreement with our previous study [24], where PAC dosing to a contact tank yielded an added +15% to +18% pharmaceuticals' removal from a secondary effluent. The tested pesticides are small, neutral (except bentazone) molecules, diffusing into the carbon pores faster than larger NOM molecules.…”
Section: Cost Analysissupporting
confidence: 92%
See 2 more Smart Citations
“…Overall, and under the conditions tested, equivalent removals of pesticides and NOM were obtained with inline PAC dosing and to a contact tank in trial 1 using the same PAC dose, while in trial 2 a higher inline PAC dose was apparently required (50% higher in the conditions tested, though further testing with other PAC doses would be necessary to confirm it). Results from trial 1 are in agreement with those observed by Ivancev-Tumbas et al [25] for p-nitrophenol removal from tap water, whereas results from trial 2 are more in agreement with our previous study [24], where PAC dosing to a contact tank yielded an added +15% to +18% pharmaceuticals' removal from a secondary effluent. The tested pesticides are small, neutral (except bentazone) molecules, diffusing into the carbon pores faster than larger NOM molecules.…”
Section: Cost Analysissupporting
confidence: 92%
“…These results point out that, under the tested conditions, a porous cake layer (with no increased resistance and easily backwashed) was formed on top of the membrane surface either with continuous inline PAC dosing or with continuous PAC dosing to the contact tank. Although longer trials might be necessary to fully confirm it, the results are in agreement with our previous study with a PAC/FeCl 3 /ceramic MF pilot for treating a secondary effluent [24]. Moreover, our previous study with similar waters [20] showed that 6-24 mg/L PAC dosing to a contact tank did not promote membrane fouling and that treatment capacity, an indicator incorporating key aspects of process productivity and energy needs, kept constant or slightly increased with PAC dosing.…”
Section: Pesticides and Organic Matter Removalsupporting
confidence: 91%
See 1 more Smart Citation
“…Other research based on the combination of various treatments for the reduction of CBZ were based mainly on the combined treatments of AC with membranes: PAC/MBR [ 134 ], MBR/PAC [ 135 ], and PAC/MF [ 136 ]. In these studies, reductions between 10% and 20% were obtained depending on the treatment and which membranes were used.…”
Section: Resultsmentioning
confidence: 99%
“…A summary of expenditures is given in Table 5. For CMF, the operational, specific, and maintenance costs were adapted from the TECHNEAU Report Heijman & Bakker (2007), a recent study conducted by Weschenfelder et al (2016), Viegas et al (2020), and NF costs adapted from Zhou et al (2015). The costs of mixing and pumping energy requirements corresponding to 0.026 kWh/m 3 for the CP-CMF process were included (Tompkins et al 2019), in a recent work with ceramic MF membrane energy consumption was given as 0.4 kWh/m 3 (Hakami et al 2020) in our study it was calculated as 0.15 kWh.…”
Section: Cost Estimationmentioning
confidence: 99%